A Federação Espírita do Rio Grande do Sul e a organização do movimento espírita rio-grandense (1934-1959) - Scherer, Bruno Cortês (2015)
This dissertation studies the organization of the spiritist movement in Rio Grande do Sul chosen as the object of analysis the performance of the Federação Espírita do Rio Grande do Sul (FERGS), between the years 1934 and 1959. Adopting as source the newspaper "A Reencarnação" edited by the institution as its official press, among other documentary evidence, identifies and reflected on its proposed institutional and doctrinal organization, considering the relationship of the entity and spiritism with other social actors and their integration in the religious field. The study points to a number of initiatives developed over this period, focusing on dissemination of spiritism, on the norms of discourse and practice rituals and defining ways of working in the social space. Asserting itself as an instance of representation able to protect spiritism and its practitioners legal constraints and the resulting oppositions of medical and religious fields, the FERGS and its proposed institutional organization emerged in this period as a consistent way to the diffusion and consolidation of spiritism in rio-grandense society. The study is part of the line of research "Migration and Labour" of the Post-Graduate in History at the Federal University of Santa Maria, Master level, with specialization "History, Power and Culture", and is linked the research project "Spiritualism, Religion and assistance in Rio Grande do Sul in the First Half of the twentieth Century."